Virtual Assistance and Virtual Guiding for Tegaren’s Technological Enhancement - Suksmawati, Herlina; Rahmatin, Leily Suci; Setiyowati, Arin; Setiawan, Tho’at; Nuryananda, Praja Firdaus (Nusantara Science and Technology Proceedings, 2023)
Tegaren stands out as one of the premier tourist destinations in Trenggalek. In both 2022 and 2023, it has been honored with a place among the top 500 recipients of the Anugerah Desa Wisata Indonesia (ADWI). This village, nestled on a hillside, also earned recognition at the 2022 Anugerah Seratus Desa Wisata Trenggalek (Sadewa). After conducting research and field visits, the previous research team identified two primary challenges facing Tegaren: 1) an aging population and 2) a lack of digital and technology-based skills among Tegaren's workforce. As a result, the proposing team has developed virtual assistance and a virtual guiding training program in collaboration with Tegaren to ensure that the local tourism sector doesn't solely rely on traditional methods but can evolve into a fully comprehensive digital village. Through the implementation of this virtual assistance and virtual guiding training program, the proposing team, along with its partners, aims to keep the tourism sector aligned with the latest technological and informational advances while enhancing the human resource capabilities within Tegaren. In addressing the issues within Tegaren, the proposing team has introduced the concept of virtual assistance and virtual guiding training, employing methodologies such as participatory rural appraisal, asset-based community development, and capacity building. This approach transforms the village community from being merely the program's target into active program participants, fostering collaboration and ensuring sustainable development for the future.